A Proportional Resonant Controller Scheme for Suppressing Resonance in Grid tied Multilevel Inverter - Hemakesavulu Oruganti; Subranshu Sekhar Dash; Chellammal Nallaperumal; Sridhar Ramasamy (Energies, 2018)
Photovoltaic (PV) resources are connected to power grid through voltage source inverters. The quality of power output from PV inverter should be in grid compliance of IEEE standard. In this regard, the deployment of appropriate low pass filters such as inductor (L), capacitor (C) or inductor capacitor inductor (LCL) is critical as they aid in minimizing the harmonics being injected into the grid. LCL filters are well entrenched but they bring in stability issue due to resonance and therefore a damping controller with suitable control logic is needed. In this work, to suppress resonance, a Proportional Resonant-Derivative (PR-D) controller has been designed, proposed, and compared with existing counterparts, i.e., two-degree of freedom controller (2DOF) and feedback current controller. The results exhibits that PR-D controller admits meliorate resonance damping and constancy when compared with the two other schemes. The whole system has been simulated in MATLAB/Simulink environment and a prototype has also been made to ensure the performance.